Application of Mike/Swat for simulation the salt intrusion – a case study in Ve river, Quang Ngai province - Long Ta Bui; Diep Thi My Le (International Association of Lowland Technology, 2020)
The coastal areas are mainly impacted via climate change. In the past century, sea level has risen averagely 10-12cm every decade and caused the serious damage in coastal region. Understanding dynamics in estuaries plays an important role in assessing physical, bio-chemical changes which are occurring, especially the salt intrusion. This research demonstrates the approach to evaluate the scope of salt intrusion at Ve estuary, Quang Ngai province via studying hydrodynamic and hydrological processes by using integrated models: SWAT/NAM/MIKE21. Based on flow, salt intrusion data measured and flow by ADCP (Acoustic Doppler Current Profilers) to validate the model. Then, the prediction of impacted scope and the level of salt intrusion in the study area are concluded.